39.6k views
1 vote
Find the average rate of change. show all work for each calculationuse aroc (average rate of change)

Find the average rate of change. show all work for each calculationuse aroc (average-example-1
User BennoDual
by
5.3k points

1 Answer

4 votes

We have to use the average rate formula


(f(b)-f(a))/(b-a)

Let's replace the points (-3,-3) and (4,2). Where a = -3, b = 4, f(a) = -3, and f(b) = 2.


(2-(-3))/(4-(-3))=(2+3)/(4+3)=(5)/(7)

Hence, the average rate is 5/7.

User Joum
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.